Fulfillment Of The Rights Of Health BPJS Patients In Health Services Based On Lawv Number 36 Of 2009 Concerning Health (Study in Palagimata Hospital) - Sofyan Febrianto; Waode Novita Ayu Muthmainna; Amrun Kahar; L.M. Ricard Zeldi Putra (AIQU: Journal Multidiscipliner of Science, 2024)
This study aims to determine the fulfillment of BPJS Patient Rights If there is a refusal in health services at the Palagimata Regional General Hospital Baubau City, to find out the Civil Law analysis of BPJS Patient Rights If there is a health services at the Palagimata Regional General Hospital Baubau City. The research method used is empirical normative with a descriptive research approach. Empirical normative research approach is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on a particular legal event that occurs in society. The results showed that legal protection of patients' rights against BPJS Health participants who experience denial of health services in hospitals is divided into two forms, namely preventive protection with repressive protection. The form of legal protection provided to BPJS Kesehatan participants for health services at the hospital is the right to claim compensation with the form of civil liability in Articles 1367 and 1365. The role of the government when it occurs in overcoming cases of denial of service in hospitals against BPJS Kesehatan participants is to increase the capacity of health service facilities, re-design the health service referral system, and optimize Minimum Service Standards.